A metallographic examination of fracture splitting C70S6 steel used in connecting rods - Aksoy, Ziya; Özdemir, Zafer; Özdemir, Tekin (Marmara Üniversitesi Fen Bilimleri Dergisi, 2012)
Microalloyed high carbon steels (such as C70S6, SMA40 and FRACTIM) have been considered to be economic alternatives to powder metal and conventional steel, having been used as main crackable con-rod materials in recent years. Compared with powder metal and conventional steel, these microalloyed high carbon steels have remarkable advantages. One of the main advantages is that cost reduction can be achieved by changing the micro-structure of the con-rod. Sawing and machining processes of the rod and cap, in order to mate two faces can be eliminated, and is believed to reduce the production cost by 25%.Another advantage of this production method is that fracture-splitting connecting rods exhibit 30% higher fatigue strength and 13% less weight than conventional connecting rods, and can be splitted into two pieces (big body and cap) by fracturing with an instant impact load.Compared with powder metal and cast con-rods, it also has lower cost for the whole manufacturing process. Hence, it provides more advantageous production opportunities, and is prefered in manufacturing technology mostly.In this article, the metallographic and fracture surface analysis have been investigated using optical and SEM method. Hardness of C70 steel is also determined. In the article it has been made clear that, the microstructure of the fracture-split con-rod has a fine grain size with densely pearlite because of its high carbon content.Also it is shown that a high hardness value is determined approximately 280-300 HB. Almost no deformation exhibits after splitting into 2 pieces, which is what any con-rod productor would like to expect when utilizing C70S6 crackable steel in production phase.
Keywords: connecting rod; fracture splitting; metallographic examination; crackable C70S6 steel